ANALISIS PROFITABILITAS BANK SYARIAH DAN BANK KONVENSIONAL PERIODE 2010-2015 - Radestian Radestian (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
This study aims to analyze the profitabilitybetween Islamic Banks and Conventional Banks in Indonesia. This study uses data from 2010 to 2015. The samples used in this study consists of 3 Islamic Banks and 3 Conventional Banks. While the data used is obtained from the financialstatements of each bank stored in the bank website address. Data analysis technique is done by t-test and regression analysis with SPSS 18 application. The estimation results on the t-test showed that the banks used in this study did not have significantmean differences. The result of the regression test shows simultaneously the independent variable of DPK, Equity and Loan only affects the ROA of conventional bank. While partially on conventional banks DPK has a negative effect is not significantto ROA, Equity has a positive effect is not significantto ROA, Loans has a positive effect is not significantto ROA. In Islamic banks DPK has a positive effect is not significantto ROA, Equity has a negative effect is not significantto ROA, Loans has a negative effect is not significantto ROA. From these results can be said that conventional banks more profitablewhen compared to Islamic banks.